The nature and origin of the cult of Silvanus in the Roman provinces of Dalmatia and Pannonia - Perinić, Ljubica (Archaeopress Roman archaeology, 2016)
This volume deals with the cult of Silvanus and presents the evidence and current state of research of the cult in Dalmatia and Pannonia to the wider scholarly community. New perceptions on the subject are proposed and a fresh standpoint from which certain problems may be (re)addressed is presented.